ENSURING HUMANE CONDITIONS: THE ROLE OF LEGISLATION IN PROMOTING PRISONERS’ WELFARE IN NIGERIA - Adeyemi, Olubunmi James .; Okonkwo, Chinwe Helen (Ayden International Journal of Law, Political Science, and Administration, 2024)
Regardless of the offense committed or the duration of their imprisonment, individuals in custody, whether convicted or awaiting trial, retain their human rights and dignity. This paper delves into the legislative framework governing prisoners' rights in Nigeria. It emphasizes the importance of humane treatment and respect for the fundamental dignity of all prisoners.